KEPEMIMPINAN SERVANT LEADERSHIP RELIGIUS DI MTSN 5 KLATEN - Ulil Nur Hidayati; Istanto Istanto (JURNAL TARBIYAH, 2025)
This study aims to describe the characteristics and practices of religious servant leadership at MTsN 5 Klaten, focusing on how the principal integrates the values of service, exemplary conduct, and Islamic spirituality in daily leadership. A qualitative phenomenological approach was employed through observation, interviews, and documentation, with data validity tested using source and technique triangulation. Data analysis followed the interactive model of Miles and Huberman, including data reduction, presentation, and conclusion drawing. The findings reveal that the principal practices religious servant leadership through consultation, empowerment of teachers and students, habitual worship, and exemplary attitudes of trustworthiness (amanah), wisdom (fathonah), and compassion. These practices are reflected in activities such as congregational prayers, Qur’an recitation, character development, and open communication that foster a humanistic school environment. Moreover, the principal responds to digital-era challenges, such as gadget misuse, with persuasive and educational approaches. The study concludes that religious servant leadership strengthens students’ spiritual character, enhances teacher performance, and builds a harmonious Islamic school culture.Penelitian ini bertujuan mendeskripsikan karakteristik dan praktik kepemimpinan servant leadership religius di MTsN 5 Klaten, dengan fokus pada integrasi nilai pelayanan, keteladanan, dan spiritualitas Islam dalam kepemimpinan kepala madrasah. Pendekatan kualitatif fenomenologis digunakan melalui observasi, wawancara, dan dokumentasi, dengan uji keabsahan data menggunakan triangulasi sumber dan teknik. Analisis data dilakukan menggunakan model interaktif Miles dan Huberman yang meliputi reduksi, penyajian, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kepala madrasah menerapkan kepemimpinan pelayan religius melalui musyawarah, pemberdayaan guru dan siswa, pembiasaan ibadah, serta keteladanan dalam sikap amanah, fathonah, dan kasih sayang. Praktik ini tampak dalam kegiatan shalat berjamaah, tadarus Al-Qur’an, pembinaan karakter, dan komunikasi terbuka yang menumbuhkan suasana humanis. Selain itu, kepala madrasah responsif terhadap tantangan era digital dengan pendekatan persuasif dan edukatif. Penelitian ini menyimpulkan bahwa servant leadership religius memperkuat karakter spiritual, kinerja guru, dan budaya sekolah Islami.